Barriers and facilitators to the dissemination of national movement behavior guidelines among health-promoting organizations: a qualitative study - Kauffeldt, Kaitlyn D.; McFadyen, Isaac K.; Latimer-Cheung, Amy E.; Faulkner, Guy; Tomasone, Jennifer R. (Frontiers in Public Health, 2024)
BackgroundNational movement behavior guidelines offer evidence-informed recommendations for how to obtain health benefits. However, their impact on practice and policy has been limited. Factors at multiple levels determine the effective mobilization of knowledge into practice. Historically, little attention has been paid to assessing the social, organizational, and economic factors that influence the uptake of national movement behavior guidelines; potentially contributing to their blunted impact on public health outcomes. The purpose of this study was to explore the barriers and facilitators experienced by intermediary organizations to disseminating national movement behavior guidelines.MethodsRepresentatives from organizations involved in the development and dissemination of the Canadian 24-Hour Movement Guidelines for Adults 18–64 Years and Adults 65 Years or Older were invited to participate in semi-structured interviews to explore barriers and facilitators to national movement behavior guideline dissemination. Interview guides were informed by the Consolidated Framework for Implementation Research (CFIR). Fourteen interviews were conducted, and transcripts were analyzed using inductive thematic analysis. Identified barriers and facilitators were mapped onto the CFIR.ResultsParticipants identified several elements that have the potential to influence the dissemination of national movement behavior guidelines, such as organizational alignment, resources (i.e., time, human, financial), and ownership of the guidelines.ConclusionThis study provides insight into the breadth of barriers and facilitators to guideline dissemination that may be experienced by intermediary organizations. Findings may be used to inform interventions designed to improve the dissemination and uptake of national movement behavior guidelines among health-promoting organizations.